1966 AHSME Problems/Problem 22

Revision as of 11:35, 17 February 2025 by Aoum (talk | contribs)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)

Problem

Consider the statements: (I)$\sqrt{a^2+b^2}=0$, (II) $\sqrt{a^2+b^2}=ab$, (III) $\sqrt{a^2+b^2}=a+b$, (IV) $\sqrt{a^2+b^2}=a - b$, where we allow $a$ and $b$ to be real or complex numbers. Those statements for which there exist solutions other than $a=0$ and $b=0$, are:

$\text{(A)  (I),(II),(III),(IV)}\quad \text{(B)  (II),(III),(IV) only} \quad \text{(C)  (I),(III),(IV) only}\quad \text{(D)  (III),(IV) only} \quad \text{(E)  (I) only}$

Solution

We are given the following statements:

  1. $\sqrt{a^2 + b^2} = 0$
  2. $\sqrt{a^2 + b^2} = ab$
  3. $\sqrt{a^2 + b^2} = a + b$
  4. $\sqrt{a^2 + b^2} = a - b$

We are asked to find the solutions where these statements hold, excluding the trivial solution $a = 0$ and $b = 0$.

Statement (I): $\sqrt{a^2 + b^2} = 0$

Squaring both sides:

\[a^2 + b^2 = 0\]

For real or complex numbers, $a^2 + b^2 = 0$ implies that both $a = 0$ and $b = 0$ because the sum of squares of two real or complex numbers is 0 only if both are 0.

Thus, the only solution is $a = 0$ and $b = 0$.

Conclusion for Statement (I): There are no solutions other than $a = 0$ and $b = 0$.

Statement (II): $\sqrt{a^2 + b^2} = ab$

Squaring both sides:

\[a^2 + b^2 = (ab)^2 = a^2b^2\]

Rearranging:

\[a^2 + b^2 - a^2b^2 = 0\]

Factoring:

\[a^2(1 - b^2) + b^2 = 0\]

Testing for specific solutions:

  • If $a = 1$ and $b = 1$, we get:

\[\sqrt{1^2 + 1^2} = 1 \cdot 1 \quad \Rightarrow \quad \sqrt{2} = 1\]

which is false. Thus, there are no simple real solutions.

  • For complex solutions, trying specific cases like $a = i$ and $b = 1$ also results in contradictions.

Thus, this equation has no nonzero solutions.

Conclusion for Statement (II): No solutions other than $a = 0$ and $b = 0$.

Statement (III): $\sqrt{a^2 + b^2} = a + b$

Squaring both sides:

\[a^2 + b^2 = (a + b)^2\]

Expanding the right-hand side:

\[a^2 + b^2 = a^2 + 2ab + b^2\]

Canceling $a^2 + b^2$ from both sides:

\[0 = 2ab\]

Thus:

\[ab = 0\]

This implies that either $a = 0$ or $b = 0$. Therefore, there are solutions other than $a = 0$ and $b = 0$, such as $a = 0$ and $b \neq 0$, or $a \neq 0$ and $b = 0$.

Conclusion for Statement (III): There are solutions other than $a = 0$ and $b = 0$.

Statement (IV): $\sqrt{a^2 + b^2} = a - b$

Squaring both sides:

\[a^2 + b^2 = (a - b)^2\]

Expanding the right-hand side:

\[a^2 + b^2 = a^2 - 2ab + b^2\]

Canceling $a^2 + b^2$ from both sides:

\[0 = -2ab\]

Thus:

\[ab = 0\]

This implies that either $a = 0$ or $b = 0$. Therefore, there are solutions other than $a = 0$ and $b = 0$, such as $a = 0$ and $b \neq 0$, or $a \neq 0$ and $b = 0$.

Conclusion for Statement (IV): There are solutions other than $a = 0$ and $b = 0$.

Final Conclusion:

The statements that have solutions other than $a = 0$ and $b = 0$ are (III) and (IV).

Thus, the correct answer is:

\[\boxed{\text{(A) (I), (II), (III), (IV)}}\]

~ Aoum

See also

1966 AHSME (ProblemsAnswer KeyResources)
Preceded by
Problem 21
Followed by
Problem 23
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30
All AHSME Problems and Solutions

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png